The influence of customer trust and artificial intelligence on customer engagement and loyalty – The case of the home-sharing industry - Chen, Ying; Prentice, Catherine; Weaven, Scott; Hisao, Aaron (Frontiers in Psychology, 2022)
Trust is an important factor in online and offline transactions. However, the role of customer trust has received limited attention in the home-sharing economy. Drawing on the revised stimulus organism response model and trust transfer theory, this paper examines how customer trust in home-sharing hosts and platforms affects customer relationships with them, manifested in customer engagement and loyalty. As artificial intelligence (AI) is extensively utilised within home-sharing platforms to facilitate business operations and enhance the customer experience, this study also examines the influence of AI on customer trust and other related outcomes. The research was undertaken in China, with respondents who had used home-sharing platforms. Results from structural equation modelling show that customer trust had a significant positive relationship with customer engagement and loyalty. Customer engagement mediates the relationship between trust and loyalty, while AI may have a negative moderating effect between host trust and customer engagement and customer engagement and loyalty. The paper contributes to sharing economy and AI research. The work has implications for practitioners offering suggestions to develop marketing strategies for business growth and sustainability.